KEDUDUKAN HUKUM KEPALA OTORITA IBU KOTA NUSANTARA DALAM SISTEM PEMERINTAHAN DI INDONESIA - Ni Made Bintang Purnama Dewi Purnama; Kaharudin; Rr. Cahyowati (Faculty of Law, University of Mataram, 2026)
This study aims to analyze the legal status of the Head of the Nusantara Capital Authority within the Indonesian governmental system and to examine the status of the legal products issued by the Head of the Nusantara Capital Authority within the hierarchy of laws and regulations. This research employs a normative legal research method using statutory, conceptual, historical, and comparative approaches. The conclusions of this study are as follows: (1) the legal status of the Head of the Nusantara Capital Authority within the Indonesian governmental system constitutes a constitutional innovation in Indonesia, introducing the concept of a Special Regional Government at the provincial level with a Head of Government holding ministerial rank, which is consistent with the 1945 Constitution of the Republic of Indonesia; (2) the legal products issued by the Head of the Nusantara Capital Authority are not included in the hierarchy of laws and regulations as stipulated in Article 7 paragraph (1) of Law Number 12 of 2011 concerning the Formation of Laws and Regulations. This is because regulations issued by the Head of the Nusantara Capital Authority do not constitute regional legal products, but rather institutional regulations equivalent to ministerial regulations established pursuant to law and recognized under Article 8 paragraphs (1) and (2) of Law Number 12 of 2011 concerning the Formation of Laws and Regulations.